2014
DOI: 10.3386/w19841
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Malpractice Law Improve Health Care Quality?

Abstract: Despite the fundamental role of deterrence in justifying a system of medical malpractice law, surprisingly little evidence has been put forth to date bearing on the relationship between medical liability forces on the one hand and medical errors and health care quality on the other. In this paper, we estimate this relationship using clinically validated measures of health care treatment quality constructed with data from the 1979 to 2005 National Hospital Discharge Surveys and the 1987 to 2008 Behavioral Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Carvell et al (2012) provide evidence that joint and several liability tort reforms have been accompanied by reductions in the non-auto, non-overdose accidental death rate. However, Frakes and Jena (2014) find only small and statistically insignificant effects of changes in malpractice pressure (in terms of non-economic damages caps) on different measures of health care treatment quality. Similarly, Sloan and Shadle (2009) conclude, based on the analysis of eight different reform types, that neither medical decisions nor patient outcomes are systematically affected by tort reforms.…”
Section: Related Work and Literature Reviewmentioning
confidence: 73%
“…Carvell et al (2012) provide evidence that joint and several liability tort reforms have been accompanied by reductions in the non-auto, non-overdose accidental death rate. However, Frakes and Jena (2014) find only small and statistically insignificant effects of changes in malpractice pressure (in terms of non-economic damages caps) on different measures of health care treatment quality. Similarly, Sloan and Shadle (2009) conclude, based on the analysis of eight different reform types, that neither medical decisions nor patient outcomes are systematically affected by tort reforms.…”
Section: Related Work and Literature Reviewmentioning
confidence: 73%
“…Eight studies evaluated the impact of caps on noneconomic damages on quality of care. 20,21,26,28,29,33,34,41 Avraham and Schanzenbach 20 found that noneconomic damages were associated with a significant decrease in mortality for those aged 45-65 years (about 1.4 percent), but no significant difference for those aged 65-90 years. Currie and Macleod observed that caps on noneconomic damages were associated with a significant increase in preventable complications of labor (6.0 percent).…”
Section: Quality Of Carementioning
confidence: 99%
“…12,16,[27][28][29][30]32,[34][35][36]38,40,[42][43][44][45][46] Twelve studies evaluated the impact of tort reform on defensive medicine by assessing health care utilization 20,22,23,25,26,28,37,38,47,49,51,52 of which two (17 percent) used a difference-in-differences specification. 28,38 Thirteen studies studied quality of care 16,20,21,26,28,29,[33][34][35]37,41,48,54 of which five (38 percent) used a difference-in-differences specification. 16,28,29,34,35 Health care spending was evaluated by eight studies…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations